Pasambahan Oral Tradition in Minangkabau Marriage Custom in Nagari Sungai Puar Palembayan Sub District Agam West Sumatra : Semiotic Analysis - Helmita Helmita; Anisa Anisa Rahmadatul Husni (Fakultas Sastra Universitas Ekasakti, 2023)
Pasambahan tradition is one type of Minangkabau oral literature. This tradition is carried out in the wedding ceremony in Minangkabau custom. Pasambahan is a conversation between the two parties concerned between the host (sipangka) and the guest (si alek) to convey the intent and purpose with respect. This study aims to determine the form of symbols, symbolic functions, and symbolic meanings contained in pasambahan (customary conversation) which is a study of semiotic science theory by Marcel Danesi (2004) and interpret pasambahan at every Minangkabau traditional wedding ceremony. In addition, this study also aims to determine the forms of Minangkabau wedding traditional clothes and the symbolic meaning contained in these clothes. The method used in this research is descriptive qualitative research method. The main data collection techniques in qualitative research are observation, in-depth interviews, and followed by a study of documentation. The data analysis techniques in this study were writing down data obtained from the field, describing pasambahan (customary conversations), verifying, collecting focused data, analyzing the data obtained, and formulating final conclusions as research findings. Based on the results of the study found 7 (seven) Minangkabau traditional wedding ceremonies in the Minangkabau community of Kanagarian Sungai Puar, Pelembayan District, Agam Regency. In addition, there are also some symbols found in pasambahan (traditional conversations) in the Minangkabau traditional wedding ceremony. This study also found several symbols attached to the Minangkabau traditional wedding attire which consisted of the clothes of anak daro (bride) and marapulai (groom). contained in the traditional Minangkabau wedding dress is a form of responsibility and life that is lived during marriage.